2001
DOI: 10.1016/s0006-3495(01)75718-9
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Evidence for Binding of Cu2+ to the C-terminal Domain of the Murine Prion Protein

Abstract: Transmissible spongiform encephalopathies in mammals are believed to be caused by scrapie form of prion protein (PrP(Sc)), an abnormal, oligomeric isoform of the monomeric cellular prion protein (PrP(C)). One of the proposed functions of PrP(C) in vivo is a Cu(II) binding activity. Previous studies revealed that Cu(2+) binds to the unstructured N-terminal PrP(C) segment (residues 23-120) through conserved histidine residues. Here we analyzed the Cu(II) binding properties of full-length murine PrP(C) (mPrP), of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
93
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 51 publications
12
93
0
Order By: Relevance
“…The only apparently discordant determination concerns experiments using EPR analysis. Although precise stoichiometries were not emphasized, spectra for two coordination geometries not seen for N-terminal fragments were indicative of two varieties of Cu(II) binding sites specific within PrP121-231 (50). One type of site was compatible with an oxygen-dependent ligation, perhaps via aspartic or glutamic acid residues and was seen at pH values Ͻ7.0 (and therefore potentially …”
Section: Metal-protein Binding and Neurodegenerative Disease-mentioning
confidence: 98%
“…The only apparently discordant determination concerns experiments using EPR analysis. Although precise stoichiometries were not emphasized, spectra for two coordination geometries not seen for N-terminal fragments were indicative of two varieties of Cu(II) binding sites specific within PrP121-231 (50). One type of site was compatible with an oxygen-dependent ligation, perhaps via aspartic or glutamic acid residues and was seen at pH values Ͻ7.0 (and therefore potentially …”
Section: Metal-protein Binding and Neurodegenerative Disease-mentioning
confidence: 98%
“…Although four of these sites were designated as belonging to the octameric repeat region, the location of the so-called fifth site has been difficult to identify. There have been three suggestions, each associated with a histidine at either amino acid residue 96 (9), 111 (12), or 187 (13,14). However, the majority of reports suggest that, if there is a fifth site, it is also in the N terminus.…”
mentioning
confidence: 99%
“…These residues are located within the tandemly repeated PHGGGWGQ sequence known as the octarepeat and at the flexible hinge that connects the N-terminal and C-terminal domains (16 -20). In addition to these, other minor Cu(II)-binding sites in the C-terminal globular domain have been reported (19,21,22). Studies with PrP C models, as synthetic peptides and recombinant forms, have shown binding stoichiometries of up to one Cu(II) per octarepeat motive in a process in which the interaction among cation sites, measured as positive cooperativity, appears when the number of sites is higher than two (15,18,(22)(23)(24).…”
mentioning
confidence: 99%